1990
DOI: 10.1182/blood.v76.9.1771.bloodjournal7691771
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of large numbers of enriched human megakaryocytes from liquid cultures of normal peripheral blood progenitor cells

Abstract: Investigations linking human megakaryocyte development and cell biology have been hindered by an inability to obtain large, relatively pure megakaryocyte cell preparations from in vitro stem cell cultures. We report here that such preparations can be generated from liquid cultures of normal human peripheral blood mononuclear cells stimulated by a serum source of megakaryocyte colony stimulating activity (Meg- CSA, the 0% to 60% ammonium sulfate protein fraction of aplastic canine serum). Adherent-depleted peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Megakaryocyte culture media consisted of IMDM (GIBCO, Grand Island, NY) supplemented with 1% Glutamine Pen-strep (Irvine Scientific, Santa Ana, CA). Preliminary experiments indicated that 20-30% normal, heparinized, platelet-poor, human AB plasma was required for megakaryocyte development, in agreement with other reports [16][17][18]. By including the following components of a serum-free culture system, the optimal concentration of human plasma could be reduced to 10%: 2-mercaptoethanol ( lo4 M), pyruvic acid (1 10 mg/ml), cholesterol (7.8 mg/ml), adenosine, guanine, cytidine, uridine, thymidine, 2-deoxycytosine, 2-deoxyadenosine, 2-deoxyguanosine (10 mg/ml each, Sigma); human recombinant insulin (10 mg/ml), human transferrin (300 mg/ml), soybean lipids (1%, Boehringer Mannheim, Indianapolis, IN); human recombinant basic fibroblast growth factor ( 2 ng/ml, Genzyme, Cambridge, MA); human recombinant epidermal growth factor (15 ng/ml), platelet-derived growth factor (10 ng/ml, Amgen, Inc., Thousand Oaks, CA).…”
Section: Mediasupporting
confidence: 90%
See 1 more Smart Citation
“…Megakaryocyte culture media consisted of IMDM (GIBCO, Grand Island, NY) supplemented with 1% Glutamine Pen-strep (Irvine Scientific, Santa Ana, CA). Preliminary experiments indicated that 20-30% normal, heparinized, platelet-poor, human AB plasma was required for megakaryocyte development, in agreement with other reports [16][17][18]. By including the following components of a serum-free culture system, the optimal concentration of human plasma could be reduced to 10%: 2-mercaptoethanol ( lo4 M), pyruvic acid (1 10 mg/ml), cholesterol (7.8 mg/ml), adenosine, guanine, cytidine, uridine, thymidine, 2-deoxycytosine, 2-deoxyadenosine, 2-deoxyguanosine (10 mg/ml each, Sigma); human recombinant insulin (10 mg/ml), human transferrin (300 mg/ml), soybean lipids (1%, Boehringer Mannheim, Indianapolis, IN); human recombinant basic fibroblast growth factor ( 2 ng/ml, Genzyme, Cambridge, MA); human recombinant epidermal growth factor (15 ng/ml), platelet-derived growth factor (10 ng/ml, Amgen, Inc., Thousand Oaks, CA).…”
Section: Mediasupporting
confidence: 90%
“…Cells fractionated by CCE were plated at 1.25 and 2.5 x lOs/ml in triplicate. The culture consisted of 15% citrated, platelet-poor, human AB plasma in Iscove's modified Dulbecco's medium (IMDM) with additives as described by Mazur et al [16] and incubated 12 days at 3 7 T , 5% C 0 2 in air. Plates were subsequently fixed with methanol:acetone, stained with antibodies to GPIb and GPIIb/IIIa (Biodesign, Kennebunkport, ME) and a secondary goat anti-mouse fluorescent isothiocyanate ([FITC], Southern Biotechnology Assoc., Inc., Birmingham, AL).…”
Section: Megakaryocyte Progenitor Cell Assaymentioning
confidence: 99%
“…An average of 4.4 rt 0.3 x lo6 CD34' cells were obtained per unit (n = 25), with an average purity of 90 f 5% (n = 12). Cells were frozen until use [38] then thawed and plated at 5 x 106/ml in megakaryocyte growth medium (meg-GM) [31] with 10% normal human AB plasma (HuAB) [39] and 10 ng/ml purified, mammalian cell-derived, rHuMGDF [ 11. After eight days, cultures were transferred to fresh culture wells and supplemented with 20-50% fresh meg-GM + 10% HuAB. Cultures were monitored for the appearance of proplatelets which occurred one to three days after replating.…”
Section: Cd34+ Cell Isolation and Culture Conditionsmentioning
confidence: 99%
“…Cord blood (CB) represents a large and readily available source of HSC. Several investigators [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] have previously made efforts to obtain megakaryocytic progenitors from HSC in bone marrow, peripheral blood, or CB by using a liquid culture system. Furthermore, there have been some clinical trials in which in vitro expanded megakaryocytic progenitors were infused to patients receiving high-dose chemotherapy.…”
Section: Introductionmentioning
confidence: 99%